Decision Support System for Election of OSIS Chair for Muhammadiyah Schools Using the Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER) Method - Winda Suci Lestari Nasution; Patriot Nusa (Talenta Publisher, 2022)
OSIS (Organisasi Intra Sekolah) is an official Student Council, which found in every school in Indonesia. The problem to be solved in a school is the need for an OSIS as a forum for students in schools to achieve the goals of coaching and developing students in accordance with the school's vision and mission. The main task of OSIS task is to achieve the goals in accordance with the school's vision and mission, therefore OSIS chair should have competencies and skills. The right decisions are needed for the implementation of the school's vision and mission. This first stage of research is performed by doing interview and survey to determine the criteria of OSIS chair. Based on interview and questionnaire has indicate that the student council member elects the chair based on several criteria consist of managerial ability, responsibility, communication and cooperation as well as discipline. The method proposed in the selection of the OSIS chairperson using simple multi attribute rating technique exploiting rank (SMARTER) approach and using Rank Order Centroid (ROC) weighting. The result of this study indicates that 75% of OSIS coaches and members need a decision-making system that can assist OSIS in making computerized decisions in determining the next OSIS chair candidate.